Let's talk handling: how to keep your canine patients' tails wagging!. Issue 12 (2nd December 2021) - Campbell, Emma J.
ABSTRACT: Veterinary visits can be stressful for canine patients, particularly during handling and restraint. Stress or fear can have a negative effect on measurable parameters, leading to inaccurate records of blood pressure and heart rate due to "white coat syndrome". There are a variety of ways and means available in order to facilitate a smoother visit for both the patient and owner alike. The veterinary practice journey begins from the waiting room to consultation room, handling and restraint to hospitalisation. Each individual a patient encounters is vital to their care and can also be important in ensuring their visit is as stress-free as possible. There are numerous adaptations that can be made not only from a handling perspective but practice layout as well as food involvement in patient care. Involving the owners in clinical exams can make all the difference. Attention to body language indicators is essential as often patients tell us when they need a break long before we give them the chance to have one. Small adjustments to everyday handling techniques can make all the difference.